Heart Rate Variability and Clinical Features as Predictors of Atrial Fibrillation Recurrence After Catheter Ablation: A Pilot Study - Saiz-Vivo, Javier; Corino, Valentina D. A.; Hatala, Robert; de Melis, Mirko; Mainardi, Luca T. (Frontiers in Physiology, 2021)
Single-procedure catheter ablation success rate is as low as 52% in atrial fibrillation (AF) patients. This study evaluated the feasibility of using clinical data and heart rate variability (HRV) features extracted from an implantable cardiac monitor (ICM) to predict recurrences in patients prior to undergoing catheter ablation for atrial fibrillation (AF). HRV derived features were extracted from the 500 beats preceding the AF onset and from the first 2 minutes of the last AF episode recorded by an ICM of 74 patients (67% male; 57 ± 12 years; 26% non-paroxysmal AF; 57% AF recurrence) before undergoing first AF catheter ablation. Two types of classification algorithm were studied to predict AF recurrence: single classifiers including Support Vector Machines (SVM), Classification and Regression Trees (CART) and K-Nearest Neighbor (KNN) classifiers as well as ensemble classifiers. The sequential forward floating search (SFFS) algorithm was used to select the optimum feature set for each classification method. The Optimum Weighted Voting (OWV) method, which used an optimum combination of the single classifiers, was the best overall classifier (Accuracy = 0.82, Sensitivity = 0.76 and Specificity = 0.87). Clinical and HRV features can be used to predict rhythm outcome using an ensemble classifier which would enable a more effective pre-ablation patient triage that could reduce economic and personal burden of the procedure by increasing the success rate of first catheter ablation.